The Phenomenon of Drug Addiction in Algerian Society: Reality and Factors - guendouz, mounir (Journal of Social Sciences and Humanities, 2016)
This study addresses the topic of drug addiction in Algerian society, exploring its reality and contributing factors. It was conducted to highlight a phenomenon that has reached dangerous dimensions in terms of its scale and the pace of its spread among various segments of society. The study begins by discussing the history of drugs and their current reality based on provided statistics, as well as the methods and factors involved, while also examining the perspective of Islamic Sharia and Algerian law on the matter. The study concludes that addiction is undergoing a dangerous evolution in terms of the availability and manufacturing of narcotic substances, as well as the methods and factors used; furthermore, it finds that promotion and drug accessibility play a significant and concurrent role in facilitating entry into the world of drugs.